Biochemical and proteomic characterization of Paenibacillus sp. ISTP10 for its role in plant growth promotion and in rhizostabilization of cadmium. (September 2018) - Kumari, Moni; Thakur, Indu Shekhar
Abstract: The plant growth promoting potential of Paenibacillus sp. ISTP10 was evaluated by biochemical assays and LC-MS/MS based proteomic analysis. The biochemical characterization showed that the strain possesses characters like N2 fixation, phosphorous solubilization (238 ± 4.78 μg/ml), production of ammonia, HCN, IAA (172.95 ± 2 μg/ml), EPS (125.74 ± 2.18 μg/ml) and siderophores. The proteomic analysis indicated the list of proteins involved in N and P metabolism, siderophores production, biocontrol activities and xenobiotic degradation were also expressed. The stain also showed resistance against Cd, Cr, Cu, Ni and Zn with MIC values of 1.8, 0.36, 2.5, 1.8 and 3.3 mM respectively. An in vivo system for studying the resistance response of cotton in Cd stressed soil showed reduced phytotoxicity and decrease in accumulation of Cd in root, shoots and leaves by 40.00%, 32.26% and 35.30% respectively, and increase in total chlorophyll content, plant height, root length, plant fresh weight, plant root and shoot fresh weight and plant dry weight. Highlights: The strain ISTP10 has been characterized for its plant growth promoting activities. LC-MS/MS analysis led to identification of proteins involved in PGPR activities. The PGPR stain ISTP10 also showed resistance against Cd, Cr, Cu, Ni and Zn. The strain ISTP10 reduced phytotoxicity and decrease accumulation of Cd in the plant. Paenibacillus sp. as a potential biofertilizer under heavy metal stressed condition.